ANALISIS MOTIVASI BELAJAR SISWA PADA PELAJARAN GEOGRAFI DIMASA PANDEMI DI KELAS X IIS 1 SMA NEGERI 9 PONTIANAK - Vina Widiyanti; Sulistyarini Sulistyarini; Agus Sugiarto (Universitas Tanjungpura, 2022)
This study aims to analyze intrinsic learning motivation and extrinsic student on geography subjects during online learning in the future the covid 19 pandemic in class X IIS 1 SMA Negeri 9 Pontianak is motivation student learning that looks there are still students who didi not complete that task given by the teacher, and the student did not dare express opinions the method used is descriptive with the type of qualitative research with case studies. the source of this research data is students class X IIS SMA Negeri 9 Pontianak. the data is the result of the geography teacher interview and students of class X IIS SMA Negeri Pontianak. data collection technique through interviews. the results showed that, (1) desire and desire successful students can be said to be good, students always try to learn seriouly. (2) a strong urge in learning is said to be good, students have an interest in studying geography. (3) hopes and ideals are said to be good, even though students have more aspirations for the future good but not related to geography. (4) awards learning given by the teacher to students is said to be good, in foster learning in students. (5) learning activites are said to be no good, students feel bored in learning geography while online because the methods used by teachers are less varied. (6) learning environment said to be good, students feel safe from the beginning to the end of the process learning geography during online learning